2010
DOI: 10.5539/gjhs.v2n1p150
|View full text |Cite
|
Sign up to set email alerts
|

An Econometric Analysis of the US Health Care Expenditure

Abstract: This paper estimates the determinants of aggregate health care expenditure function for the U.S. by applying a co integration test on a time series data. The evidence presented in the paper supports co integration. The paper lends support to the view that per capita income is the major determinant of aggregate health care expenditure in the U. S. Age of the population, the number of practicing doctors and the share of public finance do not contribute significantly to the explanation of the health care spending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Moreover, external cooperation of the WHO was also required to make an exchange of expertise and healthcare information. Das and Martin (2010) quantitatively examine the determinants of aggregate healthcare expenditure using a co-integration procedure in the USA. The results indicate that per capita income contributes significantly to the explanation of healthcare expenditure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, external cooperation of the WHO was also required to make an exchange of expertise and healthcare information. Das and Martin (2010) quantitatively examine the determinants of aggregate healthcare expenditure using a co-integration procedure in the USA. The results indicate that per capita income contributes significantly to the explanation of healthcare expenditure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There have been a considerable number of studies looking at EHS vehicle demand in North America, Australia, and other parts of the world (see summary in Table 1). These studies can be grouped into three categories: (a) spatial and temporal descriptive analysis ( 14 ), (b) diagnostic and predictive modeling ( 1517 ), and (c) location coverage and service optimization ( 1820 ). For example, Munjal et al ( 14 ) conducted a spatial and temporal analysis on requests for EHS vehicles in relation to population size and medical complaints.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They finds that income and ageing are important drivers of health expenditures. Das and Martin (2010) examined determinants of health expenditure in USA and found that practising doctors does not contribute significantly to the explanation of the healthcare expenditure.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…As a result of the studies carried out, there are studies that have reached the conclusion that the young population is not a significant influence on health expenditure, as well as studies that find that the young population is a significant influence on health expenditures (Gbesemete andGerdtham,1992, Ehikioya(2013) and Fasoranti(2015) ) Grafik. 1: Health Expenditure in Turkey (1975Turkey ( -2013 Das and Martin Das and Martin(2010) examined determinants of health expenditure in USA and found that practising doctors does not contribute significantly to the explanation of the healthcare expenditure.When looked at the study made on life expectancy from birth, the results that the health expenditures increase as the expected life expectancy from birth increases. For example, Jaba et al (2014) and Karagöz and Tetik (2009) concluded that life expectancy at birth has a significant effect on health expenditures.…”
Section: Introductionmentioning
confidence: 99%